Transforming legal aid: access to criminal defence services - Kemp, Vicky (Ministry of Justice, 2010)
With legal aid reform having the potential to change the organisation of criminal defence services a survey of users in the criminal justice system was undertaken. The findings helped to highlight potential barriers to legal advicea and further research was undertaken. The findings examine issues relating to criminal legal aid in the police station and in the magistrates court. Also explored are implications for 'client choice' of a solicitor and financial incentives operating within the legal aid reforms.